Comparative Study on the Antioxidant Activity of Monascus Yellow Pigments From Two Different Types of Hongqu—Functional Qu and Coloring Qu - Wu, Li; Zhou, Kangxi; Chen, Feng; Chen, Guimei; Yu, Ying; Lv, Xucong; Zhang, Wen; Rao, Pingfan; Ni, Li (Frontiers in Microbiology, 2021)
This study is the first to investigate the difference in the composition of Monascus azaphilone pigments (MonAzPs) between functional Qu (FQ) and coloring Qu (CQ) and analyze their relationships with antioxidant activity. The composition of key active components and antioxidant activity of the ethanol extracts of FQ and CQ were analyzed by Uv-vis, HPLC, and chemical antioxidant tests. The composition of MonAzPs of the ethanol extracts was further analyzed by HPLC-MS. Seven Monascus yellow pigments (MYPs) with high abundance were successfully purified for the antioxidation evaluation in vitro and in the cell. Correlation analysis between the metabolites and the antioxidant activity of Hongqu indicated that MonAzPs might play an essential role in the antioxidant activity (r > 0.80). By contrast, the monacolin K (MK), polysaccharide, ergosterol, and γ-aminobutyric acid (GABA) were not significantly correlated with the antioxidant activity. Orthogonal partial least squares discriminant analysis (OPLS-DA) based on the composition of MonAzPs revealed that the abundance of MYPs is significantly different between FQ and CQ (P < 0.05 and VIP > 1.0). Seven MYPs (monasfluore A, monaphilone B, monascuspilion, monascin, monaphilone A, ankaflavin, and new yellow pigment) with high abundance were successfully purified for the antioxidation evaluation. Chemical antioxidant tests revealed that the antioxidant activities of monaphilone A, ankaflavin, and new yellow pigment only from CQ were significantly more potent than monasfluore A and monascuspilion only separated from FQ. The cellular antioxidant assay (CAA) showed that the new yellow pigment had the best antioxidant activity (quercetin equivalent 7.23 μM), followed by monasfluore A and monaphilone B, all of which were significantly better than monascin and ankaflavin, the two most frequently reported MYPs. Research on the structure–activity relationship demonstrated that alterations of the hydroxyl that occurred on C-3′ or C-11 obviously affected the antioxidant activities of MYPs. Our findings provide evidence that MYPs may be the key active components for CQ to have a more potent antioxidant capacity than FQ. The alterations of the hydroxyl that occurred on C-3′ or C-11 obviously affected the antioxidant activities of MYPs.